Manual Loop in Laparoscopic Appendectomy: A Retrospective Cohort Study and Literature Review - Priyanka Ramesh; Aniqa Saeed; Muniza Nusrat; Sehrish Batool; Hina Khan; Ghulam Murtaza (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the incidence of complications [Surgical site infection (SSI), intra-abdominal abscess (IAA), stump leak] related to stump ligation with manual loop of sliding extracorporeal suture knot in LA. Methods: This cohort study was conducted on patients who underwent laparoscopic appendectomy from June 2014 to November 2020 performed by the same surgeon with almost similar technique. Stump was ligated with manual loops, applied by the surgeon or trainee or both (one by surgeon and other by trainee). SSI and IAA were classified according to Centers for Disease Control and Prevention (CDC) criteria. Results: Total 120 patients were included with median (Interquartile range, IQR) age of 24 (19-35) years and male predominance i.e. 81 (67.5%). Median (IQR) for the duration of symptoms, time from presentation to surgery and duration of surgery was 2(1-4) days, 10 (4-15) hours and 60 (44-70) minutes, respectively. SSI was documented in 9(7.5%) patients, managed by wound hygiene and antibiotics. IAA was observed in one(0.8%) patient who required readmission for antibiotics and radiology guided drain placement. No stump leak was observed. Conclusion: Manual endo-loop is a safe, reliable and cost effective technique for stump ligation in LA, and can safely be incorporated into teaching of surgical trainees. Keywords: Surgical Site Infection, Intra Abdominal Abscess, Endoloop, Stump leak, Clips, Stapler.